VALORIZATION OF BREWER’S SPENT YEAST FOR THE EXTRACTION OF β-GLUCAN (Applied Biological Research, 2026)
Brewer spent yeast (BSY) is an underutilized byproduct of the brewery industry with significant potential as a renewable source for β-glucan extraction, contributing to a circular economy. The present study aimed to extract β-glucan from indigenous and commercial brewing yeasts using two different extraction methods. Pilsner beer was brewed using Saccharomyces cerevisiae (MK680910) for the collection of indigenous BSY, while commercial BSY was obtained from Underdoggs Brewery and Kitchen, Ludhiana, India. The BSY derivatives obtained after cell lysis and extraction were evaluated for proximate composition. The β-glucan content in indigenous BSY was 16.6 mg g⁻¹ and 15.1 mg g⁻¹ using acid–base and water extraction methods, respectively, whereas commercial BSY yielded 19.1 mg g⁻¹ and 16.5 mg g⁻¹ by the corresponding methods. β-Glucan was characterized using Fourier Transform Infrared (FTIR) spectroscopy, with characteristic absorption bands observed at 1034–1150 cm⁻¹ and 889 cm⁻¹, corresponding to C–O–C stretching vibrations of polysaccharides. The acid–base extraction method proved more efficient than water extraction, producing higher yields with fewer impurities. This study highlights the potential of BSY as a cost-effective and scalable source of β-glucan, offering value-added applications for the brewing industry and related sectors.
Keywords: Acid-base extraction; β-glucan; brewer’s spent yeast; FTIR; water extraction